As imagens da cultura sertaneja na literatura de cordel - Brito, Alexsandro Bastos de (2016)
This study sought to bring on overview of how the Cordel Literature arrives in Brazil and build over the time, an own identity of production, circulation and construction standard. Through the flyers, we present and noted how they can be used to combat racism that still persists in Brazil. The Popular culture, placed at the beginning by the intellectuality as if it needed help of this society segment to stay alive, can’t be seen anymore as static, but perceived as a source of revelation and knowledge construction. The corpus of this work are the flyers of Rodolfo Cavalcante and Franklin Maxado, two great exponents of Cordel Literature in the northeast of Bahia. These flyers, as well as entertainment and information, proved themselves true historical documents. In this sense, hidden figures by society, as the slave of the nineteenth century, Lucas da Feira, gain the opportunity, through the verses from Cordel, to prove themselves as memory. Coupled to these questions we have as focus on this study, to realize popular culture and its signs in Cordel Literature.